Use and Evaluation of Online Public Access Catalogue in the Central Library of Banaras Hindu University: A Study - Shekhar, Chandra; Sonkar, S. K. (Journal of Information and Knowledge, 2018)
This paper examines Online Public Access Catalogue (OPAC) usage by the students, research scholars and members of faculty of Banaras Hindu University Library. A questionnaire-based survey of various categories of users such as faculty members, research scholars, graduate and postgraduate students, covering different disciplines such as Arts, Science, Engineering, Medicine and Agriculture sciences was conducted. The paper discusses various aspects such as awareness, frequency of use, purpose, problems and satisfaction level of users, etc. The results of the study show that only one third of the respondents used OPAC frequently. The study also found that majority of users consulted OPAC to know the availability and location of the requisite documents.